Quality Enhancement through Incorporating Studentcentered Learning Methods in Higher Education Institutions (HEIs) - Khabeishvili, Guranda; Tvaltchrelidze, Nino (European Scientific Journal, ESJ, 2021)
One of the main tasks of higher education institutions is to attract their customers with its quality education. To improve education practices and to meet the challenges of an ever-changing environment, it is vital to introduce a paradigm shift in education. Hence, what we teach to our students is not enough, the way we teach them is what matters the most. There are several factors, which can serve as indicators of quality education. The demands, needs, expectations of the learners have changed. Accordingly, the primary goal of education is to provide the quality that ensures contemporary students not only with subject knowledge but also with the key skills needed for the 21st century world. Although the concept of student-centeredness is not new, challenges still exist concerning incorporating all characteristics and elements of the student-centered learning approach in Higher Education Institutions in Georgia. According to the previous studies, it is noticeable that the lack of resources and staff training are some of the hindering factors to create and maintain student-centeredness in HEIs (Tvalchrelidze & Alkesidze, 2019). The paper sheds light on the significance of making the classroom environment student-centered, as it can boost and maintain the quality of education for all students (Harris, Spina, Ehrich & Smeed, 2013; Vavrus, Thomas, Bartlett, 2011). The primary objective of this paper is to identify teachers’ perceptions of student-centered learning, along with the current instructional practices and challenges in the case of Higher Education Institutions in Georgia. Hence, it examines the level of integration of studentcentered strategies in the classrooms. For this reason, the quantitative paradigm was applied, as the methodology for the research. The research was carried out among lecturers from three different universities. The results depict that there is still a gap between the practical application of the student-centered learning methods and the perception of the concept, which can have an impact on ensuring quality education. Based on the gained data, it could be seen that less than 40% of lecturers from three different universities fully integrate student-centered learning methods. Furthermore, the research reveals some barriers that hinder the process of promoting the student-centered learning environment. Consequently, based on the findings the conclusions and recommendations were made. To deal with the hindering factors that were identified through this research, it is vital to modify and enhance institutionallevel approaches.